The Game is Changing: insurance reloaded - Mishra, K C; Mishra, Simita (India : ICFAI University Press, 2005)
Business
Keywords: Game; Changing; Insurance; Insurance Reloaded; Insuranse Sector; Life Insurance; Reinsurance; Bancassurance; Health Insurance; Insurance Investments; Insurance Industry; Micro Insurance